Bacteriophage nanofiber fabrication using near field electrospinning - Sugimoto, Ryota; Lee, Ju Hun; Lee, Ju Hyuck; Jin, Hyo Eon; Yoo, So Young; Lee, Seung Wuk (RSC Advances, 2019)
M13 bacteriophage (phage) nano- and microfibers were fabricated using electrospinning. Using liquid crystalline suspension of the phage, we successfully fabricated nano- and microscale pure phage fibers. Through a near field electrospinning process, we fabricated the desired phage fiber pattern with tunable direction and spacing. In addition, we demonstrated that the resulting phage fibers could be utilized as an electrostatic-stimulus responsive actuator. The near field electrospinning would be a very useful tool to design phage-based chemical sensors, tissue regenerative materials, energy generators, metallic and semiconductor nanowires in the future.
Keywords: Fiber patterns; Liquid-crystalline suspensions; M13 bacteriophage; Near-field electrospinning; Regenerative materials; Semiconductor nanowire